Eastward bound: Exploring the enigmatic trade of Japanese Red Seal ships in Southeast Asia during the 15th to 17th century - Dar, Ku Boon; Luan, Vu Duong (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research aims to examine the historical influence of the Japanese Red Seal ship trade on Southeast Asia during the early modern era. This study investigates the historical origins, underlying reasons, and subsequent consequences of the Red Seal ship system for both Japan and the Southeast Asian nations that participated in it. This study centres on the trade routes of these ships within Southeast Asia, with a particular emphasis on notable destinations such as Indochina, Siam, the Philippines, Cambodia, and Tonkin (present-day Vietnam). This study aims to analyse the dynamics of commerce among Japanese merchants, Southeast Asian cultures, and European colonial powers, with a specific focus on the impact of such trade on local markets and economies in Southeast Asia and Japan. This study aims to fully comprehend the Japanese Red Seal ship trade in Southeast Asia through a meticulous analysis of historical records, archival materials, and existing scholarly works. This study significantly enhances our comprehension of Japan’s early modern international trade and its interrelations with Southeast Asia, illuminating the regional dynamics’ intricacies during that particular era. In summary, this analysis underscores the considerable importance of the Red Seal ship trade in Japan’s involvement with Southeast Asia, its extensive economic ramifications, and its central role in influencing diplomatic ties among Japan, Southeast Asian nations, and Western colonial powers during that specific era.